Mesoporous Silica MCM-41 as a Carriers Material for Nystatine Drug in Delivery System - Albayati, Talib M.; AlKafajy, Ali M. (Al-Khwarizmi Engineering Journal, 2019)
In the present study, MCM-41 was synthesis as a carrier for poorly drugs soluble in water, by the sol-gel technique. Textural and chemical characterizations of MCM-41 were carried out by X-ray diffraction (XRD), Fourier transform infrared (FTIR), scanning electron microscope (SEM), and thermal gravimetric analysis (TGA). The experimental results were analyzed mesoporous carriers MCM-41. With maximum drug loading efficiency in MCM-41 determined to be 90.74%. The NYS released was prudently studied in simulated body fluid (SBF) pH 7.4 and the results proved that the release of NYS from MCM-41 was (87.79%) after 18 hr. The data of NYS released was found to be submitted a Weibull model with a correlation coefficient of (0.995). The Historical data experimental design facilitated the formulation and optimization of sustained discover the optimal formulation to loading drug, combine process variables, mixture components and categorical factors in one design.